Using games to enhance learning and teaching : a beginner's guide - Whitton, Nicola; Moseley, Alex. (New York : Routledge, 2012)
'Despite growing interest in digital game-based learning and teaching, such as alternate reality games and virtual worlds, until now most teachers have lacked the resources and technical knowledge to create games that meet their needs. The only realistic option for many has been to use existing games which too often are out of step with curriculum goals, require high-end technology, and are difficult to integrate.This book offers a comprehensive solution, presenting five principles of games that can be embedded into traditional or online learning and teaching to enhance engagement and interactivity. Contributors highlight strategies and solutions for digital game design, showing how educationally sound games can be designed using readily accessible, low-end technologies. The authors are established researchers and designers in the field of educational games. Case studies explore specific academic perspectives, and featured insights from professional game designers provide an explicit link between theory and practice. Practical in nature, the book has a sound theoretical base that draws from a range of international literature and research'--
'Until now, most teachers have lacked the resources and knowledge to create games that meet their needs. This book presents five principles that can be embedded into traditional or online learning and teaching to enhance engagement and interactivity' --
Includes bibliographical references (p. [199]-206) and index.
Keywords: Educational games; Computer games; Education -- Computer network resources